Vliv vývoje ekonomiky Německa na hospodářskou výkonnost České republiky v letech 1993-2005 - Janíčko, Martin, 1983-; Urban, Luděk, 1927-2013; Šindel, Jaromír, 1981-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2007)
The most important aim of the thesis is to find out how strong was the impact of the German economic development on the Czech economy from 1993 to 2005, through what kind of linkages could have been such an impact effective, and what are the future prospects in this field
Vedoucí práce: Luděk Urban
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2007
Rok obhajoby 2007
Keywords: národní hospodářství [obor dipl. práce]; diplomové práce; master's theses